Analysis of Students' Errors in Solving Story Problems Based on Newman's Error Analysis (NEA) on the Subject Matter of Linear Program in View of Students' Mathematical Ability - Suci Ramadhani; Dasa Ismaimuza; Sukayasa Sukayasa; Welli Meinarni (IKIP Mataram, 2024)
This study aims to describe the types of errors of students in class XI SMA Negeri 1 Sirenja in solving story problems of linear program material based on Newman's Error Analysis in terms of mathematical ability. This type of research is qualitative research with a descriptive approach. The subjects in this study were based on the results of prerequisite tests with two-variable linear inequality material with consideration of students who made the most mistakes, were able to communicate well and recommendations from mathematics teachers with one student with high, medium and low mathematics abilities. Data collection techniques in this study were written tests and interviews in the form of one essay question and interview guidelines. The interview technique used was semi-structured conducted with selected students to ascertain the types of errors made in solving story problems. The results of this study show that the errors made by subjects with high mathematics ability (ST) made mistakes in writing the final answer (encoding error). Errors made by subjects with moderate mathematics ability (SS) made errors in process skills (process skill errors), and errors in writing the final answer (encoding errors). Errors made by low ability subjects (SR) made errors in understanding the problem (comprehension error), errors in changing the problem into mathematical form (transformation error), errors in process skills (process skill error), and errors in writing the final answer (encoding error).